Залежність між альфа-1-А-адреноблокувальною активністю та квантово-хімічними показниками похідних апорфіну - Чекман, І.С.; Небесна, Т.Ю.; Бабіч, П.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The quantitative structure-activity relationships for 19 aporphine derivatives are described, and the dependence between alpha-1-A-adrenoblocking properties of these substances and their quantum-chemical parameters is studied. All molecules were optimized by the molecular mechanical (MM+) and semi-empirical (PM3) methods. Regression analysis showed a functional relation between the alpha-1-A-adrenoblocking activity of aporphine derivatives and charges on atoms C8, C11, C4 and such topological descriptors as the total valence degree, topological diameter, total connectivity, and Wiener index. Alpha-1-A-adrenoblocking activity increases with the negative charge on carbon atoms C11 and C4.